Effect of Environmental Social Governance Disclosure on Company Value in the Energy Sector Listed on the Indonesia Stock Exchange - Makarim, Faiz Firdaus; Pertiwi, Tri Kartika; Warmana, G. Oka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research is based on the fact that many companies ignore the environment in their operations, although good relationships with the community and the environment are vital for business sustainability. This responsibility increases as the company grows in size, which is reflected in the implementation of Environmental, Social, and Governance performance. (ESG). The study assessed the impact of ESG disclosure on the value of energy sector companies listed on the Indonesian Stock Exchange (BEI) in the period 2019-2022, using panel data regression analysis through EViews 12 software. The results show that ESG disclosure has an impact on the company's value. Statistical tests indicate that the disclosures of ESG have a positive effect on the company's value. However, when the interaction between ESG Disclosure and the size of a company is included in the model, the results show a negative impact. The size of the enterprise has a positive impact on company value but weakens the relationship between the ESG revelation and company value when interacting with ESG.